2024
DOI: 10.1039/d3ta07189h
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-incorporated crystalline/amorphous heterophase cobalt vanadium selenide nanoplates with dense interfacial sites for robust lithium–sulfur batteries

Pengcheng Tan,
Yuan Yin,
Daoping Cai
et al.

Abstract: The practical applications of lithium-sulfur (Li-S) batteries are severely impeded by the shuttle effect of soluble lithium polysulfides (LiPSs), sluggish redox reaction kinetics, and insulating nature of sulfur and its...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…The doping of nitrogen atoms brings abundant active sites and improves the carbon conductivity to realize more practical lithium-sulfur batteries with excellent performance at low temperatures. [42] In 2016, Shaoyin et al [43] used nitrogen-enriched carbon and carbon/sulfur composite as raw materials to prepare the proper carbonization with the good low-temperature electrochemical performance. The electrochemical evaluation of the nitrogenenriched carbon/sulfur composite cathode indicated that a reversible capacity of 368 mAh g À 1 (0.5 C) over 100 cycles was achieved at À 20 °C.…”
Section: Improved Cathodementioning
confidence: 99%
“…The doping of nitrogen atoms brings abundant active sites and improves the carbon conductivity to realize more practical lithium-sulfur batteries with excellent performance at low temperatures. [42] In 2016, Shaoyin et al [43] used nitrogen-enriched carbon and carbon/sulfur composite as raw materials to prepare the proper carbonization with the good low-temperature electrochemical performance. The electrochemical evaluation of the nitrogenenriched carbon/sulfur composite cathode indicated that a reversible capacity of 368 mAh g À 1 (0.5 C) over 100 cycles was achieved at À 20 °C.…”
Section: Improved Cathodementioning
confidence: 99%